Seagrass canopy structure mediates putative bacterial pathogen removal potential - Liu, Songlin; Wu, Yunchao; Luo, Hongxue; Ren, Yuzheng; Jiang, Zhijian; Zhang, Xia; Fang, Yang; Liang, Jiening; Huang, Xiaoping (Frontiers in Marine Science, 2023)
Bacterial pathogen removal function in seagrass meadows is gaining attention worldwide, with enhancing particle sedimentation as the main potential mechanism. Unfortunately, seagrass meadows are declining to patchiness and fragmentation due to anthropogenic activities and global climate change. However, the effects of seagrass decline on bacterial pathogen removal potential are poorly understood, limiting our ability to understand coastal-living humans and marine organisms that suffered pressure from diseases and other health-related effects in response to seagrass decline. Here we investigated abundance of putative bacterial pathogens (including Vibrio spp., Salmonella spp., Staphylococcus spp., and Enterococcus spp.) in trapped particles under different canopy structures of Enhalus acoroides patches in South China Sea. The abundance of Vibrio spp., Salmonella spp., and Staphylococcus spp. trapped particles, respectively, was observed much greater in seagrass patches with high density and height than other patches, and significantly positive correlations with seagrass density and height were observed. This was mainly ascribed to seagrass patches of high density and height being able to trap more particles. Surprisingly, however, the Enterococcus spp. abundance showed negative correlations with density and area. Enterococcus spp. is generally inhibited in well-oxygenated environments, of which the microenvironment of dissolved oxygen might be mediated by seagrass density and area. Overall, this research suggests that the potential of removal of putative bacterial pathogen was inhibited in fragmented seagrass meadow; therefore, coastal-living humans and marine organisms might suffer from an increasing risk of diseases due to the decline of seagrass meadows.